The role of school principals in developing teachers’ abilities to use e-learning in Liwā' Al-Muwaqqar secondary schools from the teachers’ point of view - Al-Zaben, Aiysha Finkhair Atallah AlRuwaished (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the role of school principals in developing teachers’ abilities to use e-learning in Liwa Al-Muwaqar secondary schools from the teachers’ point of view, and to use the descriptive analytical approach as it is the most appropriate to achieve the objectives of this study. After extracting its psychometric characteristics (honesty and stability), it consisted of (216) male and female teachers, and the results of the study indicated that the role of school principals in developing teachers’ abilities to use e-learning in its dimensions (support and dissemination of e-learning culture, achieving training needs for teachers and qualifying them, and practicing Strategic planning, and infrastructure readiness) in Liwa Al-Muwaqar secondary schools from the teachers’ point of view came average, as it came after achieving the training needs of teachers and rehabilitating them in the first place, and came in the second place after (supporting and spreading the culture of e-learning), and in the third place it came after (infrastructure readiness), and in the last place came after (and the practice of strategic planning), and there are no significant differences between Statistical variables of the study (gender, experience, and educational qualification) in the role of school principals in developing teachers' abilities to use e-learning in Liwa Al-Muwaqar secondary schools from the teachers' point of view. Education departments and professional development programs within schools in the field of e-learning.
Keywords: the role of school principals; teachers' capacity development; e-learning; male and female teachers